The Role of Renewable Energy in ReducingCarbon Emissions in Cirebon District - Nurfalah, Agni; Setiawan, Bakti; Dewayanto, Nugroho (ASEAN Journal of Systems Engineering, 2025)
The adverse effects of the use of fossil energy such as global warming make people slowly decrease the use of fossil energy including in the electric power generation sector. Emissions from burning fossil fuels such as carbon dioxide are one of the components that make up and dominate the composition of greenhouse gases. It is this greenhouse gas that prevents the sun's heat from being reflected back into the atmosphere, so that it accumulates over many years which causes the temperature of the earth's surface to increase.               Slowly the use of fossil energy is stopped and replaced with new renewable energy which produces less greenhouse gases. In meeting the demand for electricity supply, Cirebon Regency is still relying on Steam Coal Power Plants to supply electricity demand. According to projection, Cirebon's total electricity demand will be 109.860,28 GWh by 2050. If Cirebon still continues to use Steam Coal Power Plants until 2050 it's estimated that it will emit 100.489.721,74 tons of carbon dioxide emissions.               Cirebon Regency has alternative energy potential from municipal solid waste (MSW) that can be utilized. Every day, every person in Cirebon Regency can produce 0,541 kg of waste. From the observations, the electrical energy that can be generated and utilized from waste until 2050 is 8.360,45 GWh, of which 2.462,34 GWh is generated from organic waste and 5.898,12 GWh is generated from combustible waste.                   The electrical energy that can be generated from city waste is sufficient for 7,61% of the electricity needs of Cirebon Regency. With an energy mix scheme between PLTU and waste-based power plants, total carbon dioxide emissions can be reduced by 3,05%.